Hubungan Antara Minat dan Motivasi Dengan Hasil Belajar Fisika Siswa Kelas X SMAN 10 Banjarmasin - Yurmina Ulfah; Syubhan An'nur; Andi Ichsan Mahardika (Universitas Lambung Mangkurat, 2015)
Factors that influence learning outcomes is interest in learning and motivation to learn. Low interest and motivation of students tend to produce a low learning outcomes. This research aims to : (1) to analyze whether there is a positive and significant relationship between interest in learning with the learning outcomes, (2) to analyze whether there is a positive and significant relationship motivation to learn with the learning outcomes, (3) to analyze whether there is a positive and significant relationship between interest in learning with the motivation to learn, (4) to analyze whether there is a positive and significant relationship between interest and motivation to learn simultaneously with the learning outcomes. The study population was all students of class X SMAN 10 Banjarmasin and the sample amounted to 80 students drawn by random sampling technique. Methods of data collection using questionnaires and achievement test. This type of research is the correlation and the method of analysis used is the correlation-regression.The results rX1Y = 0,339, rX2Y = 0,399, r X1X2 = 0,513 dan rX1X2Y = 0,428.The result found (1) there is a positive and significant relationship between interest in learning with the learning outcomes, (2) there is a positive and significant relationship between motivation to learn with the learning outcomes, (3) there is a positive and significant relationship between interest in learning with the motivation to learn, and (4) there is a positive and significant relationship between interest and motivation to learn simultaneously with the learning outcomes in class X SMAN 10 Banjarmasin.